Case report of combined surgical oncologic and bariatric procedures. (2018) - Sadi, Salaam; Sugarbaker, Paul H.; Shope, Timothy
Highlights: Morbidly obese patients do get cancer and require laparotomy for resection of the malignancy. Sleeve gastrectomy can follow a successful oncologic intervention with minimal increase in morbidity and mortality. Doing the oncologic procedure, HIPEC, and then sleeve gastrectomy helps prevent tumor seeding at the gastric staple line. Patient satisfaction is high with a favorable prognosis expected from a simultaneous oncologic and bariatric intervention. Abstract: Introduction: Morbidly obese patients may require a laparotomy to resect a malignancy. In some patients the cancer resection can be combined with the bariatric procedure to concomitantly treat both diseases. Presentation of case: A morbidly obese patient with peritoneal metastases from an appendiceal mucinous neoplasm was evaluated and definitively treated with Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC), at the same time the patient was treated for morbid obesity with sleeve gastrectomy and removal of a previous laparoscopic adjustable gastric banding (LAGB). Discussion: The clinical features and treatments of a cancer patient who underwent a combined surgical oncologic and bariatric procedure is presented. A second-look cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (HIPEC) preceded a sleeve gastrectomy. At the time of surgical exploration the prognosis from an oncologic perspective was acceptable. The near total gastric resection was performed without complications. Conclusions: With short term follow-up, this patient's outcome was favorable suggesting that surgical oncologic and bariatric procedures can be combined. Further, clinical investigations are indicated in this common clinical setting.